(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article discusses the negative impact of environmental pollution and other harmful factors on the health of people living in industrial zones, focusing in particular on respiratory diseases. It analyzes the potential of early detection of these diseases using radiological examinations, especially X-ray imaging. The article also suggests the development of preventive measures and proposes the implementation of radiological screening within the healthcare system.